Case report: First Chinese patient with family partial lipodystrophy type 6 due to novel compound heterozygous mutations in the LIPE gene - Zhou, Yimeng; Zhang, Lin; Ding, Yang; Zhai, Yongzhen (Frontiers in Genetics, 2024)
Background: Family partial lipodystrophy (FPLD) is a rare autosomal dominant disease characterized by disorders of variable body fat loss associated with metabolic complications. FPLD6 has only been reported in a limited number of cases. Here, we reported a Chinese FPLD6 patient with compound heterozygous mutations in the lipase E, hormone-sensitive type (LIPE) gene.A 20-year-old female patient presented with hypertriglyceridemia, diabetes mellitus, hepatomegaly, and hepatic steatosis. Subcutaneous fat was significantly diminished in her face, abdomen, and limbs. The patient was assessed by detailed clinical and biochemical examinations. A liver biopsy showed severe lipodystrophy. In addition, there were retinal changes, peripheral nerve damage, and renal tubular injury. Sequencing was performed on extracted DNA. Genetic analysis revealed that the patient had compound heterozygous mutations in the LIPE gene: c.2497_250ldel (p.Glu833LysfsTer22) and c.2705del (p.Ser902ThrfsTer27) heterozygous mutations. Verification revealed that this mutation was inherited from her father and mother, respectively, and that they formed newly discovered compound heterozygous mutations occurring in the LIPE gene, causing FPLD6.We reported the first case of FPLD6 in China. Gene analysis demonstrated compound heterozygous mutations in LIPE in this patient. Our case emphasizes the importance of genetic testing in young patients with severe metabolic syndromes.